Design of a new multi-phase experimental simulation chamber for atmospheric photosmog, aerosol and cloud chemistry research - J. Wang; J. F. Doussin; S. Perrier; E. Perraudin; Y. Katrib; E. Pangui; B. Picquet-Varrault (Atmospheric Measurement Techniques, 2011)
A new simulation chamber has been built at the Interuniversitary Laboratory of Atmospheric Systems (LISA). The CESAM chamber (French acronym for Experimental Multiphasic Atmospheric Simulation Chamber) is designed to allow research in multiphase atmospheric (photo-) chemistry which involves both gas phase and condensed phase processes including aerosol and cloud chemistry. CESAM has the potential to carry out variable temperature and pressure experiments under a very realistic artificial solar irradiation. It consists of a 4.2 m3 stainless steel vessel equipped with three high pressure xenon arc lamps which provides a controlled and steady environment. Initial characterization results, all carried out at 290–297 K under dry conditions, concerning lighting homogeneity, mixing efficiency, ozone lifetime, radical sources, NOy wall reactivity, particle loss rates, background PM, aerosol formation and cloud generation are given. Photolysis frequencies of NO2 and O3 related to chamber radiation system were found equal to (4.2 × 10−3 s−1) for JNO2 and (1.4 × 10−5 s−1) for JO1D which is comparable to the solar radiation in the boundary layer. An auxiliary mechanism describing NOy wall reactions has been developed. Its inclusion in the Master Chemical Mechanism allowed us to adequately model the results of experiments on the photo-oxidation of propene-NOx-Air mixtures. Aerosol yields for the α-pinene + O3 system chosen as a reference were determined and found in good agreement with previous studies. Particle lifetime in the chamber ranges from 10 h to 4 days depending on particle size distribution which indicates that the chamber can provide high quality data on aerosol aging processes and their effects. Being evacuable, it is possible to generate in this new chamber clouds by fast expansion or saturation with or without the presence of pre-existing particles, which will provide a multiphase environment for aerosol-droplet interaction.